Capacity Enhancement at the Institutional Level : Three Case Studies in Telecommunications - Wilhelm, Vera; Mueller, Susanne D. (World Bank, Washington, DC, 2012)
How can the Bank or other development agencies more effectively support capacity enhancement (CE) in client countries? Is there a more systematic way to design and track capacity enhancement activities? Experience in telecom reform in Mali, Mauritania, and Morocco provides insights into the different opportunities and constraints that different countries face in implementing very similar reforms. It forms the basis for proposing a three-way framework for analyzing needs and planning capacity enhancement assistance.